Nanoarchitecting intelligently encapsulated designs for improved cancer therapy - Ye, Ying-Tong; Xia, Hong-Ying; Li, Jie; Wang, Shi-Bin; Chen, Ai-Zheng; Kankala, Ranjith Kumar (Frontiers in Bioengineering and Biotechnology, 2025)
Despite the success in exploring various aspects of origination and therapeutic strategies, cancer has remained one of the most dreadful metabolic disorders due to failure to eradicate tumors comprehensively and frequent recurrence because of acquired resistance to the drugs. Recently, several advancements have been evidenced in the fabrication of various smart nanocarriers encapsulated with multiple components. Several reasons for smart nanoencapsulation include the enhancement of the bioavailability of drugs, precise targetability to reduce adverse effects on normal cells, and the ability to enable controlled drug release rates at the tumor sites. In addition, these smart nanocarriers protect encapsulated therapeutic cargo from deactivation, responsively delivering it based on the physiological or pathological characteristics of tumors. In this review, we present various smart approaches for cancer therapy, including organic materials, inorganic components, and their composites, as well as biomembrane-based nanoencapsulation strategies. These nanoencapsulation strategies, along with practical applications and their potential in cancer treatment, are discussed in depth, highlighting advantages and disadvantages, as well as aiming to reveal the ultimate prospects of nanoencapsulation in enhancing drug delivery efficiency and targeted cancer therapy.